Interest Divergence: The Root of Losing a Passion for Teaching and Learning. - Au, Nhut Luan; Do, Thi Ngoc My; Nguyen, Dang Phuoc Hien (Journal of Education and Practice, 2024)
Purpose: Contemporary education aims to provide society with competent workers. Becoming productive citizens is a common altruistic interest that teachers and learners seek, which theoretically results in teachers' passion for sharing knowledge and learners' desire to become professionals. Surprisingly, teachers progressively fell out of love with teaching, and learners encountered a gradual erosion in their passion for learning. This paper presents the authors’ viewpoint on the origin of this psychological paradox and discusses possible prevention and remedial measures. Methodology: This narrative review is grounded in available educational literature on passion and interests. 'Interest', 'Passion for teaching', and 'Passion for learning' are primary keywords for searching literature on education. The authors review available papers, present an overall summary and narrate their viewpoint on this psychological paradox. Findings and discussions: Teaching and learning impact each other. Bilateral contributions are primary requirements for successful training. Exemplary teaching behaviours nourish the desire to learn, and responsible learning attitudes breed a passion for teaching. Policymakers should consider egoistic perspectives and utilitarian thinking as potential psychological characteristics that destabilise the original altruistic interest and can ignite interest divergence. Social factors, including financial burdens/dissatisfaction and heavy workload, ignite and widen interest divergence. Those factors influence teachers and learners in their interests in different ways and cause the split between trainers' and trainees' interests. Progressively and irreversibly, they no longer share the original altruistic goal. As the interest divergence widens, trainers consciously cease prioritising teaching, and learning becomes gradually dispassionate to students. It becomes a vicious circle. Unique Contribution to Theory, Practice and Policy: Policymakers should develop measures to prevent interest divergence rather than try to escape from the established vicious circle. Due to the complex origin of the divergence, prevention strategies should be holistic and involve multiple stakeholders from different levels. Taking account of egoism and utilitarianism, satisfying financial needs and ensuring curriculum appropriateness are effective prevention measures. Rescuing efforts should be systematic rather than fragmented. Policymakers should consider and respect human weaknesses when dealing with personal characteristics and laying financial burdens down. Minor course corrections are temporary solutions to cease the widening interest divergence.